2023
DOI: 10.1039/d2ra07571g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of regio-specific arylamine substitution on novel π-extended zinc salophen complexes: density functional and time-dependent density functional study on DSSC applications

Abstract: A series of π-extended salophen-type Schiff-base zinc(ii) complexes, e.g., zinc-salophen complexes (ZSC), were investigated toward potential applications for dye-sensitized solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
(112 reference statements)
1
2
0
Order By: Relevance
“…As depicted via particle-to-hole NTOs, the predominate contributions for both S 0 → S 1 transitions (83–96%) and S 0 → S 2 transitions (78–97%) exhibit a π–π* transition with a charge transfer characteristic, while minor contributions come from local excitation (<4% for TY1 ; 15 and 19% for TY2 ; 15 and 21% for TY3 ). A similar conclusion can be drawn according to the calculated electron–hole separation (EHS) approach. , As shown in Table , the dye TY1 (1.81 Å) shows a comparable charge transfer distance ( L ) to that for TY2 (1.95 Å) and TY3 (1.89 Å) according to the calculated EHS for lowest-energy transitions. Consequently, replacing the thienyl group with the CPDT moiety leads to limited enhancement on the charge transfer behavior as well as a subtle red shift of absorption.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…As depicted via particle-to-hole NTOs, the predominate contributions for both S 0 → S 1 transitions (83–96%) and S 0 → S 2 transitions (78–97%) exhibit a π–π* transition with a charge transfer characteristic, while minor contributions come from local excitation (<4% for TY1 ; 15 and 19% for TY2 ; 15 and 21% for TY3 ). A similar conclusion can be drawn according to the calculated electron–hole separation (EHS) approach. , As shown in Table , the dye TY1 (1.81 Å) shows a comparable charge transfer distance ( L ) to that for TY2 (1.95 Å) and TY3 (1.89 Å) according to the calculated EHS for lowest-energy transitions. Consequently, replacing the thienyl group with the CPDT moiety leads to limited enhancement on the charge transfer behavior as well as a subtle red shift of absorption.…”
Section: Resultssupporting
confidence: 74%
“…A similar conclusion can be drawn according to the calculated electron−hole separation (EHS) approach. 34,35 As shown in Table 2, the dye TY1 (1.81 Å) shows a comparable charge transfer distance (L)…”
Section: Electrochemical Properties and Theoretical Calculationmentioning
confidence: 90%
“…Hsien Hsin Chou et al studied the different substitution sites and electron donor substituents of Zn-salophen and found that the charge separation properties of TPA-substituted complexes were more pronounced with the same substitution sites. However, under the same substitution group, the effect of parasubstitution of C=N was more pronounced [30]. Our approach was to design and synthesize a series of Zn-salophen complexes (Zn-1-4) with D-A structures (Figure 1), varying the bridges of groups such as 1,4-phenyl or/and 2,7-fluorenyl between the electron donor (triphenylamine, TPA) and the electron acceptor (Zn-salophen) [31,32].…”
Section: Introductionmentioning
confidence: 95%